Event and city image: the effect on revisit intention. Issue 1 (10th June 2020) - Li, Hui; Lien, Che-Hui; Wang, Stephen W.; Wang, Tien; Dong, Weiwei
Abstract : Purpose: The purpose of this study is to investigate the influence of three sources of social representation (i.e. direct experience of an event, the media and social interaction) on tourists' formation of event image; to examine the effect of event image, satisfaction and city image on tourists' revisit intentions to the host city; and to explore the mediating role of city image. Design/methodology/approach: This study used the 28th Qingdao International Beer Festival (QIBF) as the case for verifying the relationships in the proposed model. The survey was conducted in Qingdao and 366 valid observations were collected. Structural equation modeling was used to validate the research model. Findings: Event image is found to be significantly and positively influenced by direct experience of an event and social interaction. City image and satisfaction are important predictors of revisit intention. The meaning of event image is transferred to city image. City image plays a pivotal role in mediating the effect of event image and satisfaction on revisit intention to the host city. Research limitations/implications: This study surveyed Chinese tourists attending QIBF in Qingdao and consequently the outcomes may lack generalizability. This research did not survey foreign tourists. Thus, the differences of attitudes and behaviors between Chinese and foreign tourists are not compared. Practical implications: The outcomes provide insights into how a city manager can organize an event to enhance tourists' intentions to revisit the city. Originality/value: This study represents one of the few studies that use both social representation theory and the theory of brand image transfer in examining the influence of external social contexts on tourists' formation of event image and investigates how the unique meaning of event activities is transferred to city image. In addition, the mediating role of city image is fully explored in this research. Abstract : 事件与城市形象：对重访意愿的影响效应 摘要 研究目的: 本研究的目的包括（1）探究社会表征的三个来源（事件的直接体验, 媒体影响, 社会互动）对游客事件形象评价的影响；（2）验证事件形象、满意度、城市形象对游客重访举办地意愿的影响；（3）检验城市形象的中介作用。 研究方法: 本研究以第28届青岛国际啤酒节为案例研究对象, 来验证模型中的变量关系。调研在青岛进行, 共收集有效问卷366份。通过结构方程模型来验证研究假设。 结论: 事件形象评价受到直接体验和社会互动的显著积极影响。城市形象和满意度是游客重访意愿重要的影响因素, 事件形象的内涵转移到城市形象。城市形象在事件形象和满意度对重访意愿的影响作用中起到重要的中介作用。 研究局限: 本研究对参加青岛国际啤酒节的中国游客进行调研, 结果可能缺少普适性。本研究没有调研外国游客, 缺少中外游客的态度和行为差异的对比。 实践意义: 研究结论对于城市管理者如何更好的组织事件活动以提升游客重访城市的意愿提供了新的思路。 价值: 本研究将社会表征理论和品牌形象理论应用到事件营销当中, 解释了游客事件形象评价的形成过程中外部社会情境的影响, 以及事件活动的独特内涵向城市形象转移的过程。同时, 本研究验证了城市形象在事件形象和满意度对重访意愿的影响作用中的中介作用。 关键词: 事件形象, 城市形象, 满意度, 重访意愿, 社会表征理论 文章类型: 研究论文 Abstract : Evento e imagen de la ciudad: efectos en la voluntad de volver a visitar Propósitos de investigación: (1) explorar el impacto de tres fuentes de representación social (experiencia directa de eventos, influencia de los medios, interacción social) en la evaluación de la imagen del evento de los turistas; (2) Verificar el impacto de la imagen del evento, la satisfacción y la imagen de la ciudad en la voluntad de los turistas para volver a visitar el lugar; (3) verificar el papel mediador de la imagen de la ciudad. Métodos de investigación: Este estudio toma el 28° Festival Internacional de Cerveza de Qingdao como un objeto de estudio de caso para verificar la relación de las variables en el modelo. La encuesta se realizó en Qingdao y se recolectó un total de 366 cuestionarios válidos. El modelo de ecuación estructural se utiliza para verificar la hipótesis de investigación. Conclusión: El estudio muestra que la experiencia directa de los eventos y la interacción social tienen un impacto positivo y significativo en la evaluación de la imagen del evento. La imagen de la ciudad y la satisfacción son factores importantes que influyen en la voluntad de los turistas a volver a visitar. Los resultados de la investigación muestran que la imagen de la ciudad desempeña un importante papel de mediación en el efecto de la imagen del evento y la satisfacción en la voluntad de volver a visitar. Limitaciones de investigación: este estudio encuestó a los turistas que participaron en el Festival Internacional de Cerveza de Qingdao, y los resultados pueden carecer de generalidad. Este estudio no investigó a los turistas extranjeros, solo a los turistas chinos, por eso careció de una comparación de las diferencias en actitudes y comportamientos entre los turistas chinos y extranjeros. Importancia práctica: las conclusiones de la investigación proporcionan nuevas ideas sobre cómo los administradores de la ciudad pueden organizar mejor las actividades del evento para aumentar la voluntad de los turistas a visitar la ciudad nuevamente. Valor: este estudio aplica la teoría de la representación social y la teoría de la imagen de marca al marketing de eventos, explicando el impacto de los contextos sociales externos en la formación de la evaluación de imágenes de eventos turísticos y el proceso de transferir la connotación única de las actividades de eventos a la imagen urbana. Al mismo tiempo, este estudio demuestra que el papel mediador de la imagen de la ciudad tiene un impacto de la imagen del evento y la satisfacción en la voluntad de volver a visitar.